The Role of NK and NKT Cells in Patients with Acute Brucellosis - Akbulut, H.; Ilhan, F.; Celik, I; Ozden, M.; Godekmerdan, A. (Premchand Shantidevi Research Foundation, 2007)
Background: The major role of T cells in Brucella immunity is secretion of gamma interferon (IFN-gamma) for activation of bactericidal function in macrophages. Natural killer T (NKT) cells are new subtype of T cells and produce IFN-gamma very quickly and promptly when they are stimulated. Therefore, NKT cells can play an effective role in immunity of brucellosis. Aim: It was aimed to evaluate whether natural killer (NK) and NKT cells have an effect on brucellosis immunity and whether there is any difference for these cell percentage between pre-and post-treatment period. Methods and Material: The study included a total of 40 acute brucellosis cases and 20 healthy subjects. Two-colour flow cytometric analysis was performed on a FACScan flow cytometer, using monoclonal antibodies CD45/CD14, isotype control and CD3/CD16+ 56. Results: No statistical significant difference was observed between patient and control groups for NKT cell counts and NK cell percentages. There were no differences between before and after treatment period in terms of NK and NKT cells ratio. Conclusion: According to our result, acute brucellosis has no effect on increasing of NK and NKT cells. To the best of our knowledge, this is the first study about NKT cells ratio in patients with acute brucellosis.
Keywords: Brucellosis; NK cell; CD1-restricted cell; NKT cell